Experimental clues of soft glassy rheology in strained filled elastomers. Issue 9 (27th February 2014) - Ehrburger‐Dolle, Françoise; Morfin, Isabelle; Bley, Françoise; Livet, Frédéric; Heinrich, Gert; Piché, Luc; Sutton, Mark
ABSTRACT Tensile stress‐relaxation measurements have been performed on a series of cross‐linked filled elastomers. The fillers are chosen to investigate the effect of the filler–filler and the filler–matrix interactions on the time dependence of the tensile relaxation modulus E(t) after UP and DOWN jumps. For the carbon black‐filled sample (strong filler–elastomer interaction) E(t) decreases as log(t) when the strain ε is strictly larger than 0.2 and reached by UP jumps. For the silica‐filled samples in the same conditions, and for all samples after a DOWN jump, including ε = 0.2, the experimental data can be fitted with a power law equation characterized by the exponent m. Thus, in all cases, |dE(t)/dt| scales as t−α with α ⩵ m + 1. Pertinence of the soft glassy rheology model for interpreting these results is examined. It is shown that α could be equivalent to the effective noise temperature x and related to the polymer chain mobility. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 647–656